Efeito do manejo de cobertura e ventilação Artificial sobre índices de conforto térmico e Desempenho de aves de corte - Araújo, Maria Angélica Gonçalves de (2011)
The animal thermal comfort depends entirely on the adequacy of facilities for environmental elements. This study aimed to evaluate covering strategies and artificial ventilation on rates of comfort and performance of broilers, males and females. There were two experimental trials. For the assessment of thermal rates, randomized design was applied in splited plots, with a 2x2 factorial arrangement of treatments, as follows: two management coverage (with and without reflective paint) and two internal management (with and without artificial ventilation), totalizing 4 treatments , evaluated for 40 days, taking the days as replicates. To evaluate the performance, it was used the same design with a 2x2x2 factorial arrangement of treatments, as follows: 2 external management systems (coverage with and without reflective paint), 2 internal management systems (with and without artificial ventilation) and 2 sex (male and female), totalizing 8 treatments. A total of 480 chicks of a day were used, Cobb lineage, sexed and randomly assigned to treatments. Each treatment consisted of 4 boxes, two boxes for males and two for females, with 30 birds each. Six birds/Box were sampled, on a total of 12 repetitions for males and 12 for females in each treatment. The studies were conducted in IFG – Urutaí Campus from december/2009 to january/2010. As environmental variables it was taken the dry bulb temperature, wet bulb, black globe, relative humidity and wind speed, and then calculated the thermal rates: THI, BGHI, ETI, RMT and RTR. For the performance evaluation the average weight was measured weekly, feed intake at the 21st and 42nd days, and mortality rate. Data were analyzed by the computer program SISVAR, through the analysis of variance and average comparison tests. The used test will be Scott Knott for environmental variables, and Tukey's test for the performance variables, considering 5% of significance for both. The combination of white paint to cover and artificial ventilation proved to be effective in improving the studied environment thermal comfort. The use of paint or artificial ventilation in an isolated way was not efficient. There are differences between the performance of males and females, with males having greater weight gain and increased feed intake compared to females, regardless of the environment in which they are. The use of simple environmental changes, such as reflective paint or artificial ventilation, promote weight gain and food consumption by broilers. There is positive effect of combined use of reflective paint and artificial ventilation on food intake by birds.